IMPACT OF COVID 19 PANDEMIC TO MARKETING TEAMS LEADERSHIP APPROACH OF START-UP COMPANIES IN INDONESIA - Muzakkir, Mizan
The COVID-19 pandemic has had a significant impact on marketing teams and leadership approaches in start-up companies in Indonesia. The sudden shift to remote work and the economic downturn caused by the pandemic have presented unique challenges for start-up companies in Indonesia. One of the main challenges faced by marketing teams in start-up companies during the pandemic has been the need to pivot their marketing strategies to meet the changing needs of consumers. With many consumers facing financial challenges and uncertainty, start-up companies have had to find ways to adapt their marketing efforts to meet these changing needs. This has often required marketing teams to be more creative and agile in their approach to marketing, using digital channels and social media to reach consumers and promote their products or services. A challenge faced by marketing teams in start-up companies during the pandemic has been the need to maintain customer relationships and support in the face of disruptions to traditional business operations. This has often required marketing teams to be more responsive and proactive in their communication with customers, using channels such as email, social media, and messaging apps to provide support and address any concerns or issues that may arise. This research is based on a descriptive qualitative approach where interviews were used to find out the leadership shift in start-up organisations. The interviews were coded in a way to categorise different types of leadership and also conflict resolutions that leaders have in their virtual marketing teams. The coding is specifically done by processing the transcript of the interviews, giving criteria and categorising each code. The results of this research indicate that employees now prefer hybrid working environments since they’ve noticed they can get more things done in a hybrid setting and also highlighting specifically on how managers or leaders are able to resolve conflict within the virtual marketing teams.